Plating of Ion‐Exchange Membranes: A Molecular Dynamics Study. Issue 12 (18th October 2022) - Truszkowska, Agnieszka; Boldini, Alain; Porfiri, Maurizio
Abstract: Electroless plating of membranes offers a viable pathway to create flexible electrodes for soft sensors and actuators, as well as flexible electronics and batteries. Ionic polymer metal composites are a promising class of active materials, realized through electroless plating of ion‐exchange membranes. The plating and electrode‐membrane interface play a key role on their performance, but computational tools to inform the selection of the plating material and optimize the plating process are currently lacking. Here, this gap is filled through the study of the electrode‐membrane interface in different types of ion‐exchange membranes via molecular dynamics simulations. Both commercially available cation‐ and research‐grade anion‐exchange membranes are studied here. For platinum coating, it is predicted that cation‐exchange membranes will have a superior interface than anion‐exchange membranes, in terms of metal penetration into the membrane, reliability of actuation performance, and interface stability. The results are in line with previous endeavors documenting the higher stability of the interface for cation‐ than for anion‐exchange membranes, easier plating processes, and better electrochemical performance when working with cation‐exchange membranes. The proposed computational framework offers a versatile environment for testing different types of coatings for specific membranes, toward optimizing the performance of electrochemical devices with plated flexible electrodes. Abstract : Plating of ion‐exchange membranes is a critical step to create flexible electrodes for soft sensors and actuators. Yet, no computational tool to optimize the plating process is currently available. Molecular dynamics simulations could serve as a benchmark to inform the selection of plating materials, as demonstrated in this comparative study that explores the stability of different composites of ion‐exchange membranes.